2022
DOI: 10.3390/agronomy13010032
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nematodes as a Means of Conservation of Soil Predatory Mites for Biocontrol

Abstract: Numerous lab and field studies have reported the potential of soil predatory mites for the biological control of plant-parasitic nematodes and arthropods pests. Most of these studies have utilized biocontrol agents in augmentative releases, essentially controlling the pest with the released predators. While this may be a valid approach, we hypothesize that conservation of soil mite predators with available, suitable, and accessible free-living nematodes as prey, will provide better agricultural ecosystem perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 240 publications
0
3
0
Order By: Relevance
“…Despite their potential benefits, these technologies have not yet been widely adopted in practical use due to various drawbacks. Biological control agents, such as predatory mites [58][59][60] and nematodes [61], are often expensive and have limited effectiveness in large-scale applications. Physical methods [62][63][64], such as high-temperature treatment and vacuum cleaning, are time-consuming and labor-intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their potential benefits, these technologies have not yet been widely adopted in practical use due to various drawbacks. Biological control agents, such as predatory mites [58][59][60] and nematodes [61], are often expensive and have limited effectiveness in large-scale applications. Physical methods [62][63][64], such as high-temperature treatment and vacuum cleaning, are time-consuming and labor-intensive.…”
Section: Discussionmentioning
confidence: 99%
“…We note that soil gamase mites participate in the establishment of ecological equilibrium in biocenoses, using soil herbivorous nematodes as prey. The mite G. aculeifer is bred on a large scale in the countries of Europe, Asia and North America for use in biological control of harmful twoflies, thrips and mites [19]. The author found that the mite Ph.…”
Section: The Place Of Gamaze Mites In the Biocoenosismentioning
confidence: 99%
“…Aggregation pheromones gather all non-feeding male and female mites of different life phases in one place to aggregate them and save them from the harsh environment (Mul et al, 2015;Carr and Roe, 2016;Chiluwal et al, 2020;Rueda-Ramírez et al, 2023). There are two main causes of mites showing aggregation behavior.…”
Section: Aggregation Pheromonesmentioning
confidence: 99%